(untitled) (Configurazioni. Research on contemporary poetry, 2023)
The article gives some cues for the analysis of Carlo Bordini’s I costruttori di vulcani (2010) from a macrotextual and secondly metrical point of view, pointing out the compromise between constructive and deconstructive instances. The survey of this peculiar “book of books” draws further depth from a comparison with poetry collections from the 1975-1984 period and the earlier auto-anthology Pericolo (2004), as well as from an in-depth study of the author’s poetics supported by archival materials.